Rehabilitasi Mental Spiritual bagi Pecandu Narkoba di Pondok Pesantren Salafiyah Condro Mowo - Khoiriyah, Alvina; Widodo, Widodo (J+PLUS UNESA, 2023)
A drug addict is basically a person who has a mental disorder, a spiritual mental emptiness seen from a religious perspective. The government has made efforts to reduce the adverse effects of drug addicts on society. Such efforts can be done with rehabilitation. Condro Mowo Salafiyah Islamic Boarding School is one of the Islamic boarding schools that has a rehabilitation program guided by holistic and comprehensive education. The formulation of the problem raised regarding the spiritual mental state of drug addicts, spiritual mental rehabilitation. The benefits of this research are expected to enrich knowledge and ideas about dealing with drug addicts. This study used a qualitative approach. Research data were collected through interviews, observation, and documentation. The results showed that the rehabilitation carried out at the Condro Mowo Salafiyah Islamic Boarding School is in the form of non-medical rehabilitation with ruqyah therapy and spiritual guidance, prayer, dhikr, istighosah and ruqyah, and reading the Qur'an. This rehabilitation effort is a series of religious guidance with divine elements.